Pengembangan Media Komik Digital (MEKODIG) dalam Upaya Meningkatkan Minat Belajar Siswa Sekolah Dasar - Rizki Purwatresna Senjaya (Jurnal Ilmu Pendidikan Dasar Indonesia, 2022)
This research was conducted by looking at the educational situation, especially in elementary schools because of the lack of variety in teaching in terms of the use of digital learning media. The lack of variety of learning media makes students less enthusiastic in participating in learning activities. The purpose of this digital comic development research is to develop a variety of teaching through digital comic media so that it can increase students' motivation and enthusiasm in teaching. The development of this digital comic research uses Research and Development (R&D) as well as a 4D development model which includes the stages, namely Define, Design, Development and Dissemination. The subjects in the study consisted of the principal and class V teacher of Purwamekar State as experts and students as trial subjects for digital comic products. Types of data collection is done by doing observations, interviews, and questionnaires. The data were analyzed using descriptive qualitative and quantitative descriptive analysis techniques. The research results are as follows. The expert test was the principal and grade 5 teacher of SD Negeri Purwamekar with a percentage of 88% test results and product trials on students with a very good percentage. Thus the results of the study, it was concluded that the learning media of digital comics in learning science for vertebrates and invertebrates in elementary schools can foster enthusiasm and be effective in learning.